PREVALENCE OF MENTAL HEALTH ISSUES AMONG TEENAGE MOTHERS IN BASE SECTOR, RULINDO, RWANDA. - Utamuriza Celine, Dr. Eugenia Nkechi Irechukwu (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Teenage pregnancy is a major health concern because of its association with higher morbidity and mortality for both the mother and the child. Childbearing during adolescence is known to have adverse social consequences, particularly regarding educational attainment, as women who become mothers in their teens are more likely to drop out of school. The general objective of this study was to examine the psychological impact of teen pregnancy on mental health within Rwandan society, focusing on the Base sector in Rulindo from 2022 to 2024. Guided by three Specific Objectives this study aimed to assess the prevalence of mental health issues among teenage mothers in the Base Sector of Rulindo, Rwanda. The study was guided by the Attachment Theory, introduced by John Bowlby in the 1960s. The research design selected for this study was a cross-sectional descriptive research design utilizing a survey questionnaire. The target population for this study was 118 teenagers in the Base Sector of Rulindo district, Rwanda, who became pregnant before the age of 19. The sample size for this research study comprised of 91 teenagers who were regarded as the study participants or respondents. The sample size for this research was determined using Yamane’s formula. The sampling techniques employed by this study was simple random and convenience sampling techniques. Data analysis involved cleaning and organizing quantitative data from the questionnaire, calculating descriptive statistics, and identifying themes in qualitative data from interviews. Triangulation was used to compare and contrast findings, ensuring validity. Results were presented clearly, using tables, graphs, and narrative descriptions to highlight implications for policy and practice. The finding from the investigation revealed significant relationships between socio-psychological factors and mental health outcomes among teenage mothers in the Base Sector of Rulindo, Rwanda. Stigmatization was a key factor, with those "Always" experiencing it having higher odds of mental health issues (OR = 3.12, p < 0.001), which remained robust in multivariate analysis (OR = 2.45, p = 0.005). Access to mental health services was critical, with better accessibility associated with lower odds of mental health problems (OR = 2.67, p < 0.001). Cultural beliefs positively influenced outcomes (OR = 2.94, p < 0.001), and peer support reduced mental health issues (OR = 2.50, p < 0.001). Isolation strongly predicted poor outcomes (OR = 3.18, p < 0.001). Educational attainment also impacted mental health, with no formal education linked to higher mental health issues (OR = 2.50, p = 0.002). Family, community, and healthcare support systems played protective roles, with significant associations in both bivariate and multivariate analyses (p < 0.01). In conclusion the study revealed that stigmatization and limited access to mental health services negatively impact the mental health of teenage mothers. Protective factors include cultural beliefs, peer support, family, and community assistance. Lower education levels are linked to poorer mental health, emphasizing the need for educational support. Recommendations focused on reducing stigma, improving healthcare access, and strengthening support systems. The researcher suggested that future research should explore the long-term effects of stigma reduction, mental health service integration, and the role of digital tools in providing remote support for teenage mothers.